Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Effect of reduced particle size on the magnetic properties of chemically synthesized BiFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Here, we report the effect of reduction in particle size on the temperature dependent magnetization of chemically synthesized BiFeO3 nanocrystals with average grain size of 55 nm. The X-ray photoelectron spectroscopy results show a significant broadening of binding energy peaks associated to Fe3+ 2p(3/2) core levels due to the reduced size. Additionally, due to the nanosize effect, the M-H loops show a significant coercivity starting from 390 K with an anomaly located in the vicinity of 150 K in our H-c vs T as well as M-r/M-s(50 kOe) vs T curves. At this temperature, both H-c and M-r/M-s(50 kOe) undergo minima. Additionally, our results for the first time show the evidence of existence of a low temperature anomaly due to spin-glass transition in the range from 40-44 K in the field cooled magnetization curves. In bulk single crystals, this transition is reported to be situated at around 50 K, however, this transition remained so far undiscovered in the recent studies on BiFeO3 nanoparticles due to the insufficient temperature resolution. The significant shift in this transition toward lower temperature can be attributed to size dependent effects. Our results clearly present new information on the size dependent properties of BiFeO3 nanoparticles.

Effect of particle size and annealing on spin and phonon behavior in TbMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2011)
Interest has grown to study TbMnO3 as it was recently reported to show a gigantic magnetoelectric effect. Here, we report the synthesis and detailed magnetic and Raman spectroscopy study on TbMnO3 particles of size similar to 25 nm and 2-3 mu m, respectively. The incommensurate-commensurate (lock-in) transition, usually observed at 27 K for bulk phase of TbMnO3 was not observed in susceptibility versus T curve but was seen at 30 K in the coercivity versus T curve in similar to 25 nm particles. This transition, which is due to the spin modulation length scale, gets weakened in nanosize due to the increased intrinsic lattice strain observed in 2-3 mu m particles, due to the effect of increased particle size. The increased value of magnetization in the 2-3 mu m sample was attributed to double exchange interactions between Mn+3 and Mn+4 spins. The role of annealing related effects on the fate of the Neel temperature for TbMnO3 was investigated. Raman spectroscopy indicated a decrease in the lattice distortion for similar to 25 nm particles. (c) 2011 American Institute of Physics. [doi:10.1063/1.3563571]

Extracellular biosynthesis of water dispersible, protein capped Mn5O8 nanoparticles using the fungus fusarium oxysporum and study of their magnetic behavior - Uddin, Imran; Poddar, Pankaj (Journal of Nanoengineering and Nanomanufacturing, 2013)
Nanomaterials of different sizes, shapes and compositions are being synthesized by various chemical, physical and biological routes. The pressing need of the hour is to have a synthesis protocol which does not harm the environment in any way and is inexpensive so that the benefits can be reaped by all. In this regard, the biological synthesis routes weigh over the chemical and physical ones which are toxic and expensive respectively. The biological routes occur at ambient conditions of temperature, pressure and pH and help protect the ecosystem as these do not employ any hazardous chemicals. Moreover, the nanoparticles obtained via biological routes are naturally protein capped which prevents their agglomeration and helps them retain their shape, size and stability for several months. One such important material is manganese oxide (Mn5O8) which at the nanoscale, has found good use in catalysis and as ionic conductors in fuel cells or batteries. The compound Mn5O8 exists in mixed valences of Mn2+ and Mn4+ and has drawn attention due to its antiferromagnetic nature. Here we report extracellular biosynthesis of manganese oxide (Mn5O8 nanoparticles in the size range of 10–11 nm at room temperature by challenging the fungus Fusarium oxysporum with manganese (II) acetate tetrahydrate [(CH3CO2)2 Mn · 4H2O] as precursor. The Mn5O8 nanoparticles so formed were characterized by TEM, XRD, FTIR, XPS, and TGA. Two mixed manganese ion valencies (Mn2+ and Mn4+) of Mn5O8 have been confirmed by XPS studies and antiferromagnetic transitions by magnetic measurements.